The Effectiveness of Turmeric Extract (Curcuma longa) to Increase The Shelf Life of Duck Meat - Febrianta, Harvey (SEEIJ (Social Economics and Ecology International Journal), 2022)
Duck meat is considered a healthy food because it contains various nutrients, such as protein, fat, as well as various types of vitamins and minerals, which are needed by the body. This meat can also be an option for people who don't like chicken meat. The nutritional content in duck meat is quite easy to decay. This study aims to determine the benefits of turmeric extract on sensory parameters consisting of taste, odor, and overall acceptability. Duck meat is marinated using turmeric extract with a percentage of between 2% - 6%, then stored at 4â„ƒ for 6 days. On 0, 3rd, and 6th days the sensory parameters were observed. The research treatments were as follows: DB0: Control duck meat, DB1: Duck meat with the addition of 2% turmeric extract, DB2: Duck meat with the addition of 4% turmeric extract, DB3: Duck meat with the addition of 6% turmeric extract. Assessment of sensory parameters are as follows: (1) dislike a lot; (2) dislike a little; (3) neutral; (4) like a little; and (5) like a lot. The panelists who assessed each sensory parameter were somewhat trained panelists of 30 people. The results of the sensory quality research found that the DB3 treatment was the best treatment. Panelists preferred the BD3 treatment compared to other treatments, especially from the taste factor and overall acceptability. The conclusion obtained from this study is that the addition of turmeric extract is able to inhibit the process of decomposition of duck meat until the 6th day, as evidenced by the taste and overall acceptability that the panelists can still accept.